Polymer microparticle dispersion, polymer microparticle-containing resin molded product, and method for producing said resin molded product
Patent Information
- Application Number
- JP2021098454
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-03
- Filing Date
- 2021-06-14
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-06-14
AI Technical Summary
【0012】 本発明のポリマー微粒子分散体は、DMF,DMAc等の有機溶媒中にカルボキシル基含有ポリマー微粒子が良好に分散したものである。このため、本発明のポリマー微粒子分散体は、有機溶媒系樹脂の成型物へのカルボキシル基含有ポリマー微粒子の練り込みに好適に使用できる。さらに、かかるポリマー微粒子分散体を使用して作製した本発明のポリマー微粒子含有樹脂成型物は、樹脂成型物内にカルボキシル基含有ポリマー微粒子を微細かつ均一に保有した素材となることから、該微粒子に由来する吸湿発熱性能、消臭性能、抗ウイルス性能等を有効に発現することができる。このため、本発明のポリマー微粒子含有樹脂成型物は、吸湿発熱性能、消臭性能、抗ウイルス性能等を求められる衣料品、寝装寝具、日用雑貨、内装材、医療用資材などの材料として好適に利用できる。
Smart Images

Figure 0007644412000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer particle dispersion, more specifically, to a carboxyl group-containing polymer particle dispersion having a solubility parameter (SP value) of 20 (MPa). 1 / 2 The present invention relates to a polymer fine particle dispersion dispersed in the above organic solvent. [Background technology]
[0002] Synthetic fibers such as polyester fibers, nylon fibers, and even polyurethane elastic fibers generally have poor moisture absorption and release properties because they contain a small amount of hydrophilic functional groups, unlike natural fibers such as cotton, wool, and silk. For this reason, various hydrophilic treatments have been proposed, as follows:
[0003] Techniques for improving the moisture absorption and release properties of polyurethane elastic fibers are known (for example, see Patent Document 1), and a technique for kneading in hydrophilic polyurethane with high water absorption of about 1800% has been disclosed, which prevents the material from falling off during washing and maintains a high texture. However, this material has drawbacks such as a slow moisture absorption rate.
[0004] Also, a technology is known in which highly moisture absorbing and releasing fine particles are produced by introducing a crosslinked structure into an acrylonitrile polymer, hydrolyzing the polymer with sodium hydroxide or the like, and kneading the resulting carboxyl group-containing polymer fine particles into polyurethane fibers (see, for example, Patent Document 2). In this example, there are reports that moisture absorbing and heat generating properties are exhibited, and the moisture absorption speed is expected to be fast.
[0005] Here, such carboxyl group-containing polymer microparticles are obtained as an aqueous dispersion having a particle size of about 0.5 μm during production, and therefore, in order to knead these into polyurethane fibers using N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc) as the solvent for the spinning dope, it is necessary to remove the moisture in advance by drying, solvent replacement, etc. However, this moisture removal results in aggregates with particle sizes of about several μm to several tens of μm, which cannot be redispersed into primary particles in DMF or DMAc by general operations such as heating and stirring.
[0006] For this reason, in addition to removing moisture, grinding etc. was also required during kneading, which was not desirable from a cost perspective. Furthermore, if the material was not ground sufficiently and particles of about several tens of micrometers remained, this could cause clogging of the nozzle during polyurethane fiber spinning, which could lead to a shutdown of operations, which was an issue. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2000 / 047802 [Patent Document 2] JP 2005-048297 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been invented in view of the current state of the prior art, and aims to provide a polymer microparticle dispersion suitable for kneading into molded articles of organic solvent-soluble resins such as polyurethane fibers. More specifically, the present invention aims to provide a polymer microparticle dispersion in which carboxyl group-containing polymer microparticles are dispersed in an organic solvent without becoming large in particle size due to aggregation. Furthermore, the present invention aims to provide a resin molded article using the carboxyl group-containing polymer microparticle dispersion and imparting functions such as moisture absorption and heat generation performance, deodorizing performance, and antiviral performance derived from the microparticles. [Means for solving the problem]
[0009] As a result of sincere efforts to solve the above problems, the present inventors have found that carboxyl group-containing polymer fine particles having many acid carboxyl groups or Li salt carboxyl groups can be well dispersed in hydrophilic organic solvents such as DMF and DMAc, and have arrived at the present invention. That is, the present invention has the following features. (1) Polymer fine particles having a total carboxyl group content of 1 to 12 mmol / g, and 80 mol % or more of the total carboxyl groups being acid carboxyl groups and / or Li salt carboxyl groups. (However, those having a maleimidyl group are excluded.) However, the solubility parameter (SP value) is 20 (MPa). 1 / 2 A polymer fine particle dispersion, characterized in that the polymer fine particle dispersion is dispersed in the above organic solvent. (2) The polymer microparticle dispersion according to (1), wherein the particle diameter of the polymer microparticles is 10 nm or more and less than 1000 nm. (3) The polymer particle dispersion according to (1) or (2), wherein the content of the polymer particles is 1 to 40% by mass.
[0010] (4) Solubility parameter (SP value) is 20 (MPa) 1 / 2 The main component is a resin that is soluble in the above organic solvents, and the total amount of carboxyl groups is 1 to 12 mmol / g and 80 mol % or more of the total carboxyl groups are acid carboxyl groups and / or Li salt carboxyl groups. A resin molding containing polymer microparticles, characterized in that the polymer microparticles are contained in the resin molding in a dispersed state with sizes of less than 1000 nm. (5) The polymer microparticle-containing resin molding according to (4), wherein the polymer microparticle content is 3% by mass or more. (6) The polymer microparticle-containing resin molding according to (4) or (5), characterized in that the saturated moisture absorption rate at 20° C. and a relative humidity of 65% is 2% or more.
[0011] ( 7) A polymer fine particle dispersion according to any one of (1) to (3) and a solubility parameter (SP value) of 20 (MPa). 1 / 2 A method for producing a resin molding containing polymer fine particles, comprising obtaining a mixture by mixing the above-mentioned resin soluble in an organic solvent, and molding the mixture. ( 8 ) Furthermore, it includes adjusting the salt type of the carboxyl group in the polymer microparticles by treatment with an alkaline compound or salt ( 7 ) A method for producing a resin molding containing polymer fine particles according to the present invention. Effect of the Invention
[0012] The polymer microparticle dispersion of the present invention is a well-dispersed polymer microparticle containing carboxyl group in an organic solvent such as DMF or DMAc. Therefore, the polymer microparticle dispersion of the present invention can be suitably used for kneading the carboxyl group-containing polymer microparticle into a molded product of an organic solvent-based resin. Furthermore, the polymer microparticle-containing resin molded product of the present invention produced using such a polymer microparticle dispersion is a material having fine and uniform carboxyl group-containing polymer microparticles in the resin molded product, and can effectively exhibit the moisture absorption heat generating performance, deodorizing performance, antiviral performance, etc. derived from the microparticles. Therefore, the polymer microparticle-containing resin molded product of the present invention can be suitably used as a material for clothing, bedding, daily necessities, interior materials, medical supplies, etc., which require moisture absorption heat generating performance, deodorizing performance, antiviral performance, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in detail below. The total amount of carboxyl groups in the polymer microparticles used in the present invention is 1 to 12 mmol / g, preferably 3 to 10 mmol / g, and most preferably 4 to 8 mmol / g. If the total amount of carboxyl groups is less than 1 mmol / g, the functions such as moisture absorption and heat generation performance, deodorizing performance, and antiviral performance are not fully exhibited when kneaded into a resin molded product, which is not preferable. If the total amount of carboxyl groups exceeds 12 mmol / g, the polymer microparticles have a very high water absorption, and the viscosity of the aqueous emulsion containing the polymer microparticles obtained in the production method described below becomes significantly high, making it difficult to remove the water thereafter, which is not preferable.
[0014] In the above-mentioned polymer microparticles, 80 mol % or more of the total carboxyl groups are acid carboxyl groups and / or Li salt carboxyl groups. If it is less than 80 mol %, it is not preferable because after removing water from the aqueous emulsion containing the polymer microparticles, it cannot be sufficiently redispersed in an organic solvent such as DMF or DMAc, and the number of aggregated particles of about several μm to several tens of μm increases. In the present invention, "-COOH" is referred to as an acid carboxyl group, and a group in which "H" is replaced by another cation is referred to as a salt carboxyl group. The salt carboxyl group is described by clearly indicating the cation type as necessary.
[0015] The polymer particle dispersion of the present invention has a solubility parameter (SP value) of 20 (MPa). 1 / 2 The organic solvent is dispersed in the above organic solvent. The organic solvent is not particularly limited, but includes DMF, DMAc, methanol, ethanol, dimethyl sulfoxide, ethylene glycol, N-methylpyrrolidone, etc., and a mixture of these organic solvents is also acceptable. The solubility parameter (SP value) here is the square root of the cohesive energy density (unit: MPa) 1 / 2 ) which is the energy required to break the intermolecular bonds contained in a unit volume.
[0016] In addition, the particle diameter of the polymer fine particles in the polymer fine particle dispersion of the present invention is preferably 10 nm or more and less than 1000 nm, and particularly preferably 50 nm or more and less than 800 nm. Regarding particles with a diameter of less than 10 nm, it is difficult to prepare them, and there is a high possibility that they will aggregate, and they are highly likely to exist in the organic solvent as aggregated particles of about several μm to several tens of μm, which is not preferable. On the other hand, when the particle diameter is 1000 nm or more, even a small amount of aggregation will result in a size of about several μm, and there is a possibility that the nozzle will be clogged when kneaded into a resin molded product. In addition, the specific surface area of the particles will be small, and the moisture absorption rate of the resin molded product containing the polymer fine particles described later may be significantly reduced, which is not preferable.
[0017] The content of the polymer particles in the polymer particle dispersion of the present invention is preferably 1 to 40% by mass based on the total mass of the dispersion. If the content is less than 1% by mass, a very large amount of dispersion is added when kneading a sufficient amount of polymer particles to express the function into a resin molding, which is not preferable because the resin is diluted with the organic solvent. If the content is more than 40% by mass, the polymer particles tend to aggregate, which is not preferable.
[0018] The method for producing the polymer microparticle dispersion of the present invention may be, for example, a method in which an aqueous dispersion of acrylonitrile-based polymer microparticles is used as a starting material, which is hydrolyzed with an alkaline compound or the like to generate carboxyl groups, and then the carboxyl groups are converted to acid type and / or Li salt type with an acid or salt or the like to produce an aqueous dispersion of carboxyl group-containing polymer microparticles, which are then further dehydrated and dispersed in an organic solvent. The method will be described below.
[0019] First, the composition of the acrylonitrile-based polymer in the aqueous dispersion of acrylonitrile-based polymer microparticles used as a raw material is desirably 40% by mass or more, preferably 50% by mass or more, and may be 100% by mass. Monomers that can be copolymerized with acrylonitrile are not particularly limited, and include monomers such as allylsulfonic acid, p-styrenesulfonic acid, acrylic acid, methyl acrylate, ethyl acrylate, and vinyl acetate.
[0020] In addition, such an aqueous dispersion of acrylonitrile-based polymer fine particles can be produced in accordance with a known polymerization method. However, since it is preferable for the fine particles to be extremely fine particles of the order of microns or less when they are ultimately kneaded into a resin molding, it is preferable to use emulsion polymerization, macroemulsion polymerization, or the like.
[0021] Next, as a method of hydrolysis using an alkaline compound, a means of adding a basic aqueous solution such as an alkali metal hydroxide or ammonia and performing heat treatment can be mentioned. In addition, in order to obtain polymer microparticles having Li salt-type carboxyl groups, it is preferable to use lithium hydroxide as such an alkaline compound. The conditions for making the total amount of carboxyl groups in the polymer microparticles 1 mmol / g or more can be easily determined by clarifying the relationship between the amount of carboxyl groups introduced and reaction factors such as reaction temperature, time, and drug concentration through experiments.
[0022] The conversion treatment of the carboxyl groups to the acid form is not particularly limited, but may be a method of treating with a mineral acid such as hydrochloric acid or nitric acid or an organic acid such as acetic acid, or a method of mixing an ion exchange resin with the aqueous dispersion of the obtained polymer microparticles to perform an ion exchange treatment. In particular, when it is desired to avoid the remaining salt by-product of the conversion treatment to the acid form, the treatment with an ion exchange resin is most preferable. In addition, the conditions for making the acid carboxyl groups 80 mol % or more of the total carboxyl groups are not particularly limited, and can be easily determined by clarifying factors such as the reaction temperature and time, and the concentration of the agent through experiments.
[0023] Regarding the conversion of carboxyl groups to Li-salt form, in addition to the method of obtaining Li-salt form carboxyl groups using lithium hydroxide during hydrolysis as described above, a method of obtaining Li-salt form carboxyl groups by neutralizing the acid-type carboxyl groups with lithium hydroxide after the conversion to the acid type as described above can also be adopted. In particular, in the case of the latter method, the ratio of the Li-salt form and the acid-type carboxyl groups can be freely adjusted. Although the Li-salt form carboxyl groups have better moisture absorption performance than the acid-type carboxyl groups, they tend to be less dispersible in organic solvents. However, by adjusting the ratio of the Li-salt form carboxyl groups and the acid-type carboxyl groups using this method, polymer microparticles suitable for a wider range of usage modes can be obtained.
[0024] Next, the polymer fine particle aqueous dispersion obtained as described above was dissolved in DMF, DMAc, or the like having a solubility parameter of 20 (MPa) or less. 1 / 2 The polymer particles are dispersed in the organic solvent described above. Examples of the dispersion method include a method of drying the aqueous dispersion of polymer particles using a device such as a spray dryer that instantly dries the polymer particles into particles, mixing the resulting polymer particles with the organic solvent described above, and dispersing the particles by heating and stirring or ultrasonic irradiation, and a method of mixing the aqueous dispersion of polymer particles with the organic solvent described above, and evaporating only the water by heating to replace the solvent. However, in the solvent replacement method, it is necessary that the organic solvent does not form an azeotropic mixture with water, and examples of such organic solvents include DMF, DMAc, etc.
[0025] The polymer microparticle dispersion of the present invention described above is a well-dispersed polymer microparticle containing carboxyl group in an organic solvent such as DMF or DMAc, and can be suitably used for kneading the polymer microparticle containing carboxyl group into a molded product of an organic solvent-based resin, and can impart moisture absorption and heat generation performance, deodorizing performance, antiviral performance, etc. derived from the polymer microparticle containing carboxyl group to the molded product of the organic solvent-based resin. In particular, since the polymer microparticles can be kneaded in a well-dispersed state, the polymer microparticles containing carboxyl group can be finely and uniformly held in the resin molded product, and the above-mentioned performances can be more effectively expressed. The polymer microparticle-containing resin molded product of the present invention obtained by using the polymer microparticle dispersion of the present invention will be described in detail below.
[0026] The polymer fine particle-containing resin molding of the present invention has a solubility parameter of 20 (MPa). 1 / 2 The main component is a resin that is soluble in the above organic solvents. Here, the solubility parameter is 20 (MPa) 1 / 2 Examples of the organic solvent include the organic solvents described above. Examples of resins soluble in such organic solvents include polyurethane, polyester, polyacrylonitrile, etc. In addition, the shape of the polymer fine particle-containing resin molded product of the present invention is not particularly limited, but examples of the main shapes include fiber, particle, film, etc.
[0027] Furthermore, in the polymer microparticle-containing resin molding of the present invention, polymer microparticles having a total carboxyl group amount of 1 to 12 mmol / g are contained in a dispersed state with a size of less than 1000 nm. Such a dispersed state is achieved by using the above-mentioned polymer microparticle dispersion as a raw material for the resin molding. When the polymer microparticles are dispersed with a size of 1000 nm or more, the microparticles aggregate with each other, resulting in a small specific surface area, and there is a risk that the moisture absorption rate and other desired functions are not fully exhibited.
[0028] In addition, the polymer microparticle-containing resin molding of the present invention preferably contains 3% by mass or more of polymer microparticles based on the total mass of the molding, more preferably 5% by mass or more, and even more preferably 7% by mass or more. If the content is less than 3% by mass, the functions such as moisture absorption and desorption derived from the polymer microparticles may not be fully exhibited, which is not preferable.
[0029] In addition, when the polymer microparticle-containing resin molded product of the present invention is manufactured using the above-mentioned polymer microparticle dispersion as a raw material, the polymer microparticle-containing resin molded product contains acid type and / or Li salt type carboxyl groups, but it is also possible to treat the polymer microparticle-containing resin molded product with an alkaline compound or salt to prepare the salt type of the carboxyl group into a salt type other than the acid type or Li salt type by ion exchange. Therefore, the salt type of the carboxyl group in the polymer microparticle-containing resin molded product of the present invention is not limited to the acid type or Li salt type. For example, when sodium hydroxide is used as the alkaline compound, it is converted into the Na salt type, which can improve the moisture absorption amount and the moisture absorption heat generation amount. In addition, when potassium hydroxide is used as the alkaline compound, it is converted into the K salt type, which can improve the moisture absorption rate and the moisture absorption heat generation rate. Furthermore, by selecting the alkaline compound or salt used for the treatment, it can be converted into the salt type of Mg, Ca, Fe, Ag, Cu, Zn, etc. in addition to Na and K.
[0030] In addition, the polymer microparticle-containing resin molding of the present invention preferably has a saturated moisture absorption rate of 2% or more at 20° C. and a relative humidity of 65%, more preferably 4% or more, and even more preferably 5% or more. If the saturated moisture absorption rate under the above conditions is less than 2%, there is a high possibility that the moisture absorption and release properties will not be realized, and the benefits will not be found, which is not preferable.
[0031] The above-mentioned method for producing the resin molding containing polymer fine particles of the present invention can be carried out, for example, by using a resin having a solubility parameter of 20 (MPa) or less. 1 / 2The resin soluble in the organic solvent is mixed with the polymer particle dispersion of the present invention, and the mixture is subjected to dry or wet molding to produce the polyurethane fiber. The method will be described below using polyurethane fiber as an example.
[0032] First, the polyurethane to be used is not particularly limited, and an example thereof includes a polyurethane polymer obtained by reacting a polyol with an excess molar amount of a diisocyanate compound to obtain a polymerization intermediate having isocyanate groups at both ends, dissolving the intermediate in an organic solvent such as DMF or DMAc, cooling the resulting mixture, and then adding a diamine compound or the like to the mixture to cause a reaction.
[0033] The dispersion of the polymer particles containing the acid type and / or Li salt type carboxyl group is added to the polyurethane polymer solution obtained as described above, and the mixture is heated and stirred to obtain a spinning solution. The spinning solution is used for spinning, drawing, etc. by a known method to produce polyurethane fibers. The spinning can be performed by any of dry spinning, wet spinning, and melt spinning.
[0034] Furthermore, in order to obtain the desired function, the above-mentioned salt type may be converted as necessary. That is, after the polyurethane fiber is produced as described above, it is possible to convert the salt type of the polymer fine particles in the fiber by treating it with an alkaline compound. There is no particular limitation on the alkaline compound to be used, but sodium hydroxide, potassium hydroxide, lithium hydroxide, etc. can be suitably used. In addition, as a treatment method, from the viewpoint of sufficiently proceeding with the reaction, a method in which the polyurethane fiber is immersed in an aqueous solution of the above-mentioned alkaline compound at a temperature of 60°C or higher is preferable.
[0035] The polymer microparticle-containing polyurethane fiber prepared as described above is capable of exhibiting functions such as moisture absorbing and heat generating properties and deodorizing properties derived from the carboxyl group-containing polymer microparticles, and is therefore suitable for use in a variety of applications including clothing such as stockings. EXAMPLES
[0036] Examples are shown below to facilitate understanding of the present invention, but these are merely illustrative and the gist of the present invention is not limited thereto. In the examples, parts and percentages are shown on a mass basis unless otherwise specified. Also, the evaluation methods for each property are as follows.
[0037] <Method for measuring the total amount of carboxyl groups> To about 1 ml (B [g]) of an aqueous dispersion of polymer fine particles having a solid content (A [%]) in 100 ml of pure water, 1.0 mol / l hydrochloric acid was added to adjust the pH to 2, and then, while stirring this with a stirrer, a 0.1 mol / l aqueous sodium hydroxide solution was added dropwise to obtain a titration curve. From the titration curve, the consumption amount (C [ml]) of the aqueous sodium hydroxide solution consumed by the carboxyl groups was determined according to a conventional method, and the amount of carboxyl groups was calculated by the following formula. Total amount of carboxyl groups [mmol / g] = 0.1 × C / (B × A × 0.01)
[0038] <Method for measuring the amount of acid-type carboxyl groups> To about 1 ml (E [g]) of an aqueous dispersion of polymer fine particles having a solid content (D [%]) in 100 ml of pure water, a 0.1 mol / l aqueous sodium hydroxide solution was added dropwise while stirring this with a stirrer to obtain a titration curve. From the titration curve, the consumption amount (F [ml]) of the aqueous sodium hydroxide solution consumed by the acid-type carboxyl groups was determined according to a conventional method, and the amount of acid-type carboxyl groups was calculated by the following formula. Amount of acid-type carboxyl groups [mmol / g] = 0.1 × F / (E × D × 0.01)
[0039] <Method for measuring the amount of Li salt-type carboxyl groups> Regarding the polymer fine particles obtained by evaporating to dryness the aqueous dispersion of polymer fine particles, the amount of Li contained was quantified by atomic absorption spectrometry, and from the result, the amount of Li salt-type carboxyl groups was calculated.
[0040] <Ratio of acid-type and Li salt-type carboxyl groups to the total carboxyl groups> It was calculated by the following formula from the results of each of the above measurement methods. Proportion of acid and Li salt carboxyl groups [mol%] = {(amount of acid carboxyl groups + amount of Li salt carboxyl groups) / total amount of carboxyl groups} × 100
[0041] <Method for measuring particle size of polymer particles in polymer particle dispersion> The volume average particle diameter was calculated from the particle size distribution expressed on a volume basis using the Zeta potential, particle size, and molecular weight measurement system ELSZ-2000ZS (manufactured by Otsuka Electronics Co., Ltd.). Note that in this measurement method, if the particle diameter exceeds 1000 nm, the volume average particle diameter cannot be calculated appropriately, so it is indicated as ">1000" in the table below.
[0042] <Method for confirming the dispersion state of polymer particles in a resin molding containing polymer particles> The resin molded product containing polymer particles is cut with a cutter, and the cross section is observed with a scanning electron microscope (SEM) at a magnification of 3000. If no polymer particles of 1000 nm or more are observed, it is determined that the particles are not coagulated to form larger particles and are in a good dispersed state.
[0043] <Method of measuring saturated moisture absorption rate at temperature of 20℃ and relative humidity of 65%RH> Approximately 1.0 g of the resin molded product containing polymer microparticles was dried in a hot air dryer at 105°C for 16 hours and the mass was measured (W1 [g]). The sample was then left in a thermohygrostat adjusted to a temperature of 20°C and a relative humidity of 65% for 24 hours, and the mass of the sample that had absorbed moisture was measured (W2 [g]). Based on the above results, the saturated moisture absorption rate was calculated using the following formula. Saturated moisture absorption rate [%]={(W2-W1) / W1}×100
[0044] <Example 1> 400 parts of acrylonitrile, 40 parts of methyl acrylate, 100 parts of divinylbenzene, 26 parts of sodium p-styrenesulfonate and 1181 parts of water were charged into a 2000 ml autoclave, and di-tert-butyl peroxide was added as a polymerization initiator at 0.5% based on the total amount of monomers, then the autoclave was sealed and polymerized at 160°C for 10 minutes under stirring. 45 parts of sodium hydroxide and 590 parts of water were added to 370 parts of the obtained aqueous dispersion of polyacrylonitrile-based polymer microparticles, and the reaction was carried out at 95°C for 36 hours to hydrolyze the nitrile group and the methyl ester group. The obtained aqueous dispersion of carboxyl group-containing polymer microparticles was adjusted to pH 2.5 with a cation exchange resin to convert the carboxyl group into an acid form. The obtained emulsion was then dried by spray drying to obtain polymer microparticles. Next, the polymer microparticles were mixed with DMAc (SP value: 22.1 (MPa) 1 / 2 The resulting aqueous dispersion of carboxyl group-containing polymer particles and the polymer particle dispersion were subjected to various evaluations, and the results are shown in Table 1.
[0045] Further, polyurethane fibers (manufactured by Asahi Kasei Corporation) are dissolved by heating in DMAc, and the above-mentioned polymer microparticle dispersion is mixed therein so that the polymer microparticles are 15% in terms of the ratio of polyurethane fibers dissolved by heating. The obtained mixture is applied to a glass plate using a bar coater #3, and then dried at 90°C for 2 hours under reduced pressure to form a film. The obtained film is then immersed in a 4% aqueous sodium hydroxide solution at 80°C for 24 hours to convert the acid carboxyl groups in the polymer microparticles to Na salt carboxyl groups, and after washing with water, the film is dried at 105°C for 1 hour to produce a film-like polymer microparticle-containing resin molding. No polymer microparticles of 1000 nm or more were observed in the obtained resin molding, and the saturated moisture absorption rate of the resin molding was 8.6%.
[0046] <Example 2> A polymer microparticle dispersion was prepared in the same manner as in Example 1, except that the agent used for hydrolysis was changed to lithium hydroxide and the subsequent treatment with a cation exchange resin was not performed. A resin molding containing polymer microparticles containing Li salt-type carboxyl groups was also prepared in the same manner as in Example 1, except that the polymer microparticle dispersion was used and the treatment with sodium hydroxide was not performed. No polymer microparticles of 1000 nm or more were found in the obtained resin molding, and the saturated moisture absorption rate of the resin molding was 7.5%.
[0047] <Example 3> In Example 1, the organic solvent for dispersing the polymer particles was methanol (MeOH, SP value: 29.7 (MPa) 1 / 2 A polymer particle dispersion was prepared in the same manner except for changing the solvent used in the preparation of the dispersion. The evaluation results are shown in Table 1.
[0048] <Example 4> In Example 1, the organic solvent for dispersing the polymer particles was N,N-dimethylformamide (DMF, SP value: 24.8 (MPa) 1 / 2 A polymer particle dispersion was prepared in the same manner except for changing the solvent used in the preparation of the dispersion. The evaluation results are shown in Table 1.
[0049] <Example 5> A polymer particle dispersion was prepared in the same manner as in Example 1, except that the amount of sodium hydroxide added during hydrolysis was changed to 27 parts. The evaluation results are shown in Table 1.
[0050] <Comparative Example 1> A polymer particle dispersion was prepared in the same manner as in Example 1, except that the treatment with a cation exchange resin was not carried out. The evaluation results are shown in Table 1.
[0051] <Comparative Example 2> In Example 1, the organic solvent for dispersing the polymer particles was methyl ethyl ketone (MEK, SP value: 19.0 (MPa) 1 / 2A polymer particle dispersion was prepared in the same manner except for changing the solvent used in the preparation of the dispersion. The evaluation results are shown in Table 1.
[0052] [Table 1]
[0053] As shown in Table 1, the polymer microparticle dispersions of Examples 1 to 5 have a particle size of 330 to 360 nm and an SP value of 20 (MPa). 1 / 2 It can be seen that the particles are dispersed in the above organic solvents without becoming large in particle size. On the other hand, the polymer microparticles of Comparative Example 1 are of the Na salt type, but the particle size is larger than 1000 nm, and it can be seen that the particle size becomes large due to aggregation. From this, it can be seen that if the type of the carboxyl group is the acid type or the Li salt type, it is possible to disperse the polymer in an organic solvent with an SP value of 20 (MPa) such as DMF, DMAc, MeOH, etc. 1 / 2 Although the above organic solvents are suitable for dispersion, it is found that the Na salt type aggregates. 1 / 2 MEK was used, but the particle size was larger than 1000 nm, and it was confirmed that the particle size increased due to aggregation. From this, the SP value was 20 (MPa). 1 / 2 Dispersibility worsens in organic solvents with lower viscosity than 20 (MPa). 1 / 2 It is therefore necessary to select an organic solvent having an SP value of at least this value.
[0054] In addition, as a result of evaluating the polymer microparticle-containing resin moldings of Examples 1 and 2, no particles with a particle diameter of 1000 nm or more were confirmed in either case, which indicates that the particles are not enlarged by aggregation even in the resin molding, and are present with the same particle diameter as in the dispersion. Furthermore, the saturated moisture absorption rate of such resin moldings is 8.6% in Example 1 and 7.5% in Example 2, so they have sufficient moisture absorption performance. From this, it can be said that when polyurethane fibers made using the polymer microparticle dispersion of the present invention are used in fabrics such as clothing, it can be expected to improve stuffiness, experience heat generation by moisture absorption, and even exhibit other functionalities derived from the polymer microparticles.
Claims
1. Polymer fine particles having a total carboxyl group amount of 1 to 12 mmol / g and 80 mol % or more of the total carboxyl groups being acid carboxyl groups and / or Li salt carboxyl groups (excluding those having maleimidyl groups) have a solubility parameter (SP value) of 20 (MPa) 1/2 A polymer fine particle dispersion, characterized in that the polymer fine particle dispersion is dispersed in the above organic solvent.
2. 2. The polymer microparticle dispersion according to claim 1, wherein the particle diameter of the polymer microparticles is 10 nm or more and less than 1000 nm.
3. 3. The polymer particle dispersion according to claim 1, wherein the content of the polymer particles is from 1 to 40% by mass.
4. Solubility parameter (SP value) is 20 (MPa) 1/2 The polymer microparticle-containing resin molding contains polymer microparticles having as its main component a resin soluble in the above organic solvent, a total carboxyl group amount of 1 to 12 mmol / g, and 80 mol % or more of the total carboxyl groups being acid-type carboxyl groups and / or Li salt-type carboxyl groups, and is characterized in that the polymer microparticles are contained in the resin molding in a dispersed state with a size of less than 1000 nm.
5. 5. The polymer fine particle-containing resin molding according to claim 4, wherein the content of the polymer fine particles is 3% by mass or more.
6. 6. The polymer fine particle-containing resin molding according to claim 4, which has a saturated moisture absorption rate of 2% or more at 20[deg.] C. and a relative humidity of 65%.
7. The polymer fine particle dispersion according to any one of claims 1 to 3 and a solubility parameter (SP value) of 20 (MPa) 1/2 A method for producing a resin molding containing polymer fine particles, comprising obtaining a mixture by mixing the above-mentioned resin soluble in an organic solvent, and molding the mixture.
8. 8. The method for producing a resin molding containing polymer fine particles according to claim 7, further comprising adjusting the salt form of the carboxyl group in the polymer fine particles by treatment with an alkaline compound or a salt.
Citation Information
Patent Citations
Polyurethane elastic fiber having improved moisture absorbing and releasing property and fabric using the same fiber
JP2005048297A
Maleimidyl group-containing material
JP2007002040A
Antiviral particle and product containing the same
JP2013147473A
Moisture-absorbing / releasing synthetic fiber and fabric using the same
WO2000047802A1
Binder for non-aqueous electrolyte secondary cell electrode
WO2018180232A1